Adverse Events in Patients With Rheumatoid Arthritis and Psoriatic Arthritis Receiving Long-Term Biological Agents in a Real-Life Setting - Mayara Costa de Camargo; Bruna Cipriano Almeida Barros; Izabela Fulone; Marcus Tolentino Silva; Miriam Sanches do Nascimento Silveira; Iara Alves de Camargo; Silvio Barberato-Filho; Fernando de Sá Del Fiol; Luciane Cruz Lopes (Frontiers Media S.A., 2019)
Background: Biological agents used for the treatment of psoriatic arthritis (PsA) and rheumatoid arthritis (RA) are associated with serious adverse effects (SAEs). Although several biologics have demonstrated good efficacy and tolerability in short-term trials, treatment guidelines recommend them as third line therapies due to a relative lack of long-term safety data.Objective: To determine the frequency and severity of adverse effects associated with the long-term use of biologics in the treatment of PsA and RA, and possible risk factors for such events in a real-life setting.Methods: We conducted a longitudinal study in PsA and RA patients only taking long-term biological agents from 2003 to 2011. Sources of information included dispensing pharmacy data and interviews with patients. Research staff conducted telephone interviews with patients inquiring about any apparent medication-related adverse drug reactions (ADRs) or SAEs. ADR/SAE's data was based on pharmacy reports. We conducted a multivariate analysis to identify the factors associated with the risk of ADRs.Results: Of the 305 patients identified, we interviewed 268 patients. Most of these were taking adalimumab 127 (47.4%), 52 (19.4%) etanercept, 42 (15.7%) infliximab, 25 (9.3%) rituximab, 10 (3.7%) abatacept, 9 (3.4%) efalizumab, and 3 (1.1%) tocilizumab. Of the 268 patients, 116 (43.3%) experienced one or more adverse events related to biological agents with 1.6 events per patient, and of these 29 (25%) experienced one or more SAEs, with majority subjected to hospitalizations. The most frequently reported ADRs were administration site reactions as observed in 73 patients (27.2%), infections in 30 patients (11.2%), effects on nervous system in 22 patients (8.2%), and 15 (5.6%) patients withdrew due to ADRs. The use of rituximab was related with less risk of ADR [PR 0.42, 95% CI 0.18-0.96; p = 0.04] than other agents. No other predisposing factors were associated with risk of ADR. The monitoring of patients (medical consultation and laboratory test) was only completed by 48 patients (30.4%).Conclusion: These data showed the early biological experience in Brazil that were associated with ADRs, withdrawals due to ADRs and SAEs. The quantification of adverse effects (serious or nonserious) considering close monitoring and patients' perceptions are increasingly important for future decision-making.